PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BUMDES SYARIAH KEMBANG SETANJUNG DESA TANJUNG MEDAN - Munawir (Fakultas Ekonomi Universitas Pasir Pengaraian, 2023)
BUMDes is a business entity whose capital is wholly or substantially owned by the village through direct participation, originating from village assets that are separated to manage assets, services, and other businesses to empower village communities as much as possible. This is so that the existence and performance of BUMDes can make a significant contribution to improving the welfare of village communities. The aims of this study were 1) to find out community economic empowerment through Kembang Setanjung Syariah BUMDes Tanjung Medan Village, 2) to find out the success achieved by Kembang Setanjung Syariah BUMDes Tanjung Medan Village in empowering the economy of the people of Tanjung Medan Village. This research is a descriptive study using a qualitative approach. The data collection techniques used in this study were interviews, observations and documentation. While the data analysis technique used is data reduction, data presentation and conclusion. The results of the study show that 1) Empowerment of the community's economy through the Kembang Setanjung Syariah BUMDes of Tanjung Medan Village in the form of a savings and loan business unit program. 2) The success achieved by the Kembang Setanjung Syariah BUMDes in empowering the Tanjung Medan Village community is community participation in encouraging BUMDes programs such as savings and loan business units and opening jobs.